Unusual expansion of CD3+CD56+ natural killer T-like cells in peripheral blood after anticytokine treatment for graft-versus-host disease: A case report. Issue 38 (September 2018) - Sheng, Lixia; Fu, Huarui; Tan, Yamin; Hu, Yongxian; Mu, Qitian; Luo, Yi; Shi, Jianmin; Cai, Zhen; Ouyang, Guifang; Huang, He
Abstract: Rationale: Basiliximab and etanercept have achieved promising responses in steroid-refractory graft versus host disease (SR-GVHD). However, the in vivo immune changes following the treatment have not been elucidated. Patient concerns: A 14-year-old boy presented with skin rash and diarrhea 20 days after haploidentical hemotopoietic stem cell transplantation. Diagnoses: We made the diagnose of grade 3 acute GVHD with skin and gastrointestinal involvement. Interventions: After the failure of the first-line treatment with methylprednisolone, combined anti-cytokine therapies with basiliximab and etanercept were prescibed. Outcomes: He achieved complete remission by basiliximab and etanercept. Furthermore, we detected that donor CD3 + CD56 + Natural killer T(NKT)-like cells expanded gradually after the period of lymphocytopenia caused by GVHD and anti-cytokine therapy. The expansion of NKT-like cells was in association with high serum IFN-γ. NKT-like cells showed preferred proliferation in response to IFN-γ and potent cytotoxicity against leukemia cells. The expansion persisted > 2 years and the patient had a leukemia-free survival of 66 months. Lessons: Our case indicated that combined anti-cytokine treatment may reset the immune system and cause NKT-like cells to exhibit a predilection for expansion.